Personality traits and exercise modes - Saraiva de Sousa, P. F. (Scientific Journal of Sport and Performance, 2023)
Over the last few decades, Physical Exercise has been touted as one of the most important behavioural health practices. Personality has been considered a predictive variable for the adoption of behaviours such as involvement in Physical Exercise programs. Therefore, this study analysed the relationship between personality and the choice of exercise modes. The literature suggests the need to investigate more on this topic. In the analysed studies, no statistically significant differences were found between personality profiles and exercise modes practiced. However, differences were found between personality profiles and aspects related to the context in which the exercise is practiced, such as intensity, space and place where they practice, whether they practice alone or accompanied and with or without the assistance of a professional. The results obtained need not only more investigation, but also need to cover more aspects related to the exercise modes practised.